DIET AND TISSUE GROWTH : I. THE REGENERATION OF LIVER TISSUE ON VARIOUS ADEQUATE DIETS. - Moise, Theodore S. (The Rockefeller University Press, 1924)
1. The toxicity of chloroform varies according to the diets used in these experiments in the following order of decreasing susceptibility of the animals: high fat > standard > high carbohydrate > high protein diets. 2. On the high fat and high carbohydrate diets there may be a more or less marked proliferation of the endothelium and the connective tissue stroma in the necrotic area producing in some instances scars resembling the picture of an early cirrhosis. 3. On the diets studied, standard, high carbohydrate, high protein, and high fat, the most active and rapid repair is observed on the standard balanced diet. On the high fat diet the reparative process is definitely delayed in comparison with the others. There are only slight differences between the high carbohydrate and high protein diets which suggest but do not conclusively show a more rapid repair with the latter diet.